2011
DOI: 10.1038/cdd.2010.176
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress activates autophagy but not the proteasome in neuronal cells: implications for Alzheimer's disease

Abstract: Protein folding stress in the endoplasmic reticulum (ER) may lead to activation of the unfolded protein response (UPR), aimed to restore cellular homeostasis via transcriptional and post-transcriptional mechanisms. ER stress is also reported to activate the ER overload response (EOR), which activates transcription via NF-κB. We previously demonstrated that UPR activation is an early event in pre-tangle neurons in Alzheimer's disease (AD) brain. Misfolded and unfolded proteins are degraded via the ubiquitin pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
86
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 40 publications
(64 reference statements)
4
86
0
2
Order By: Relevance
“…ER-associated VCP is involved in the UPR, a process that is activated by ER stress leading to the proteasomal degradation of misfolded ER proteins, called ERAD (endoplasmic reticulum-associated degradation) [38]. Interestingly, recent data imply that although UPS-mediated protein degradation is involved, autophagy seems to be the predominant degradation pathway during ER stress and UPR activation [15,16]. We found here that Washc4 deficiency resulted in ER stress in vivo without impairing the proteasomal protein degradation machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ER-associated VCP is involved in the UPR, a process that is activated by ER stress leading to the proteasomal degradation of misfolded ER proteins, called ERAD (endoplasmic reticulum-associated degradation) [38]. Interestingly, recent data imply that although UPS-mediated protein degradation is involved, autophagy seems to be the predominant degradation pathway during ER stress and UPR activation [15,16]. We found here that Washc4 deficiency resulted in ER stress in vivo without impairing the proteasomal protein degradation machinery.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the cytosolic proteasomal degradation of misfolded proteins, a process called ERAD (endoplasmic reticulum-associated degradation) [14]. Recent evidence suggests that during ER stress and UPR activation macroautophagy is the predominant degradation pathway whereas the UPS seems to play only a minor role [15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of unfolded or misfolded proteins caused by mutations in collagen genes, or saturation of protein folding capacity in ER induces ER stress, which is a potent trigger of autophagy (15). A recent study demonstrated that the interruption of correct folding of the pro-Col-I by the depletion of Hsp47 function or misfolded pro-Col-I induced their aggregation in ER, and the aggregates underwent autophagy-mediated degradation (9).…”
Section: Discussionmentioning
confidence: 99%
“…The process of autophagy involves the formation of double membrane bound vesicles called autophagosomes that envelope and sequester cytoplasmic components, including macromolecular aggregates and cellular organelles for bulk degradation by a lysosomal degradative pathway (11). Autophagy can be up-regulated in response to both external and intracellular factors, including amino acid starvation (12), growth factor withdrawal (13), low cellular energy levels (14), endoplasmic reticulum (ER) stress (15), hypoxia (16), oxidative stress (17), pathogen infection (18), and organelle damage (19). To date, more than 30 genes whose products are involved in autophagy have been identified in yeast, and these have been termed autophagy-related genes (Atg) (20).…”
mentioning
confidence: 99%
“…In a more wide-ranging consequence of posttranslational modifications of proteins, homocysteinylation of nascent protein can stall or hinder proper folding of proteins and can concomitantly activate the "unfolded protein response" (UPR) within the endoplasmic reticulum (14). Initiation of the UPR can adversely affect emerging proteins in endothelial cells (37), by extending or prolonging required activation of secreted proteins and subsequently evoking Hcy-induced oxidative stress.…”
mentioning
confidence: 99%